St. Francis of America : how a thirteenth-century friar became America's most popular saint - Appelbaum, Patricia Faith (Chapel Hill : University of North Carolina Press, 2015)
Around the nation today, St. Francis of Assisi is embraced as the patron saint of animals, beneficently presiding over hundreds of Blessing of the Animals services on October 4, St. Francis's Catholic feast day. Not only Catholics, however, but Protestants and other Christians, Hindus, Buddhists, Jews, and nonreligious Americans commonly name him as one of their favorite spiritual figures. Appelbaum traces popular depictions and interpretations of St. Francis from the time when non-Catholic Americans "discovered" him in the nineteenth century to the present.
The nineteenth century : a Protestant Catholic and Catholic Protestants -- The early 1900s : everyone's saint -- Between the wars : peace, play, and protest -- Hymn, prayer, and garden -- Postwar prosperity : embrace and resistance -- The hippie saint : counterculture and ecology -- Blessing the animals -- Living voices -- Into the future -- Epilogue -- Appendix : survey : you and St. Francis.
Includes bibliographical references and index.
Print version record.
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226.; Popular culture -- Religious aspects -- Christianity; Popular culture -- United States; United States -- Religious life and customs; RELIGION -- Institutions & Organizations; SOCIAL SCIENCE -- Sociology of Religion; Electronic books